Internalisasi Tradisi Imtihan sebagai ‘Urf Shahih dalam Pelestarian Adat Melayu di Dusun Senamat Ulu Kabupaten Bungo - Muhammad Sabli; Busriadi; Subir (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
The Imtihan tradition is a form of local wisdom in Dusun Senamat Ulu that integrates Malay custom (adat) with Islamic proselytization (syiar). However, its existence is currently threatened by digital disruption and the phenomenon of Ghazwul Fikri (invasion of ideas) among the younger generation. This study aims to describe and critically analyze the process of internalizing Imtihan local wisdom as an effort to preserve Islamic customs and culture within the community of Dusun Senamat Ulu, Bungo Regency. Utilizing a qualitative-descriptive approach with a focus on living Islam, data were gathered through participant observation, in-depth interviews with purposively selected informants, and documentary studies, which were then interactively analyzed through data condensation, data display, and verification. The results indicate that the Imtihan tradition serves as a form of ‘Urf Shahih (valid custom) internalized through the family domain based on exemplary behavior (Al-Tarbiyah bi al-Qudwah), socialization within customary institutions, and the integration of formal school curricula. However, the effectiveness of substantive value transmission is hindered by a generational communication gap, where the youth tend to dominate outer physical activities (al-amal al-zhahiri) yet remain fragile in inner comprehension due to smartphone penetration. This study recommends reconstructing preservation methods through the principle of Dakwah Bil-Asri (contemporary da'wah) based on cultural digitalization and strengthening the synergy of the Trisentris Pendidikan (three education centers). The study concludes that local wisdom can serve as an effective medium for cultural da'wah if customary institutions remain adaptive to technological transformation without losing their theological essence.